Turkey's Cyprus policy in the context of Nicosia's Presidency of the European Council: Turkey intensifies its efforts to create international legitimation for the "Turkish Republic of Northern Cyprus", to date recognised only by Ankara - Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2012)
The Cypriot presidency of the EU Council has prompted Turkey to step up its efforts to boost international recognition for its self-administrated statelet in the north of the island, using the Organisation of Islamic Cooperation (OIC) as an instrument in its endeavours. Ankara is concomitantly reacting to the current constellation of fronts in the Mediterranean, which has formed as a result of the dispute over access to recently detected gas deposits. If developments continue in the direction pursued to date, the European Union is likely to rue its indecisive policy on Cyprus and Turkey, left in the cold as far as the newly-discovered resources are concerned, while Russia increases its Mediterranean influence
Keywords: 320